Role of the amygdala in picture discrimination learning with 24-h intertrial intervals. - Gaffan, D (1994)
Six monkeys (Macaca mulatta) learned to discriminate visually between pictures of objects. Each pair of pictures was presented only once per day (24-h intervals between successive trials with the same pair). Choice of the correct picture of a pair produced immediate food reward. One set of 20 pairs was learned before operation and a second set of 20 different pairs was learned after the amygdala had been removed bilaterally in three of the monkeys. The amygdalectomized animals were severely retarded in learning the second set. These results confirm earlier results indicating that amygdalectomy impairs visual discrimination learning in tasks where the discriminanda are directly associated with the incentive value of a primary reward, and they show that, contrary to the indication of some previous results, this impairment extends to the case where each picture is seen only once per day.